PERAN KELELAHAN EMOSIONAL SEBAGAI PEMEDIASI PADA PENGARUH TUNTUTAN PEKERJAAN, DUKUNGAN SUPERVISOR, DAN REKAN KERJA TERHADAP WORK-FAMILY CONFLICT (STUDI DI PT TMNC MANUFACTURING INTERNATIONAL) - Dewangga Aji Wardana; Jati Waskito (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
The purpose of this study was to analyze the role of emotional exhaustion as a mediator in the influence of job demands, superior support, and coworkers on work-family conflict (study at PT TMNC Manufacturing International). This research method is quantitative. The population in this study were employees of PT TMNC Manufacturing International with a total of 6421 employees. The sampling technique in this study was purposive sampling and non-probability sampling. Data were collected through a survey using a questionnaire. The number of samples in this study was 125 samples. The data used in this study were primary data. The data analysis technique used path analysis with the help of statistical software with SEM-PLS. The results of this study are job demands have a positive and significant effect on emotional exhaustion. Superior support has a negative effect on work-family conflict. Coworker support has a negative effect on emotional exhaustion. Job demands have a negative effect on work-family conflict. Superior support has a negative effect on work-family conflict. Coworker support has a negative effect on work-family conflict. Emotional exhaustion has a positive effect on work-family conflict. Emotional exhaustion fully mediates from job demands to work-family conflict. The results of the coefficient test between superior support and work-family conflict indicate that specific values ​​do not have a direct effect through emotional exhaustion. The results of the coefficient test between superior support and work-family conflict indicate that specific values ​​do not have a direct effect through emotional exhaustion.